Optimalisasi pengembangan diri untuk mendongkrak prestasi (vokasional) sekolah - I Nyoman Tingkat (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2020)
Since SMAN 1 Kuta Selatan was established on 20 October 1999, its academic achievements have not yet succeeded in becoming a beacon in career achievement, although a number of alumni have succeeded in achieving master and doctoral degrees, with a proud GPA. However, it has not received a warm welcome from the workforce. On the contrary, those who achieved mediocre mediocrity in high school are now more likely to succeed in the workforce after graduation. In response to that, SMA Negeri 1 Kuta Selatan optimizes extracurriculars to boost school (Vocational) Achievement. The aim is to facilitate students’ unique talents and interests. The result was quite encouraging and became a provision for them to overcome life's problems. The results obtained from this program are that school performance has improved from year to year as seen from the achievement of trophies and awards from various competitions. The school won 52 medals in 2016, 72 medals in 2017, and it became 88 medals in 2018. The spirit of entrepreneurship among students is also increasing, which can be seen from vocational achievements. The vocational achievements seem to increase from year to year. In 2016, vocational achievement was shown by 28 students, in 2017 it became 38 students, and in 2018 it increased to 48 students after following the implementation of entrepreneurship education through the 2013 Curriculum since the 2016/2017 school year. In the end, vocational achievement also reinforces the five main values of the nation's character, namely: Religious, Mutual Cooperation, Nationalist, Integrity, and Independence.